Comparative Analysis and Simulation of the d-q Reference Frame Model of the Three Phase Induction Motor and its Modification - Olarinoye, G. A.; Abdulwahab, I. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2022)
Induction motors play an important role in residential, commercial, and industrial centers around the globe. They are rugged, reliable in operation and require low maintenance. The dynamic models of these motors are typically employed to understand their behavior in transient, steady state and under dynamic conditions. Several models of the three-phase induction motor exist in literature, but this paper proposes an alternative to the standard d-q reference frame model of the symmetrical three phase induction motor. The proposed model is obtained by modifying the standard model in a way in which the d-axis of the reference frame is aligned with the rotor flux vector. The alignment decouples the q-axis component from the d-axis component of the stator current using the vector control technique. The model is analyzed in the synchronous reference frame and then a dynamic simulation is performed. A comparison between the standard d-q reference frame model and the proposed model was performed. The simulation showed identical results of motor speed, torque and flux behavior for the two models. The difference between the two models manifests in their alternate characteristics for the d-q axes voltages and currents. It was observed that the magnitudes of the d-axis and q-axis voltages for the standard model are equal to the peak value of the applied phase voltages and zero respectively. However, the results of the proposed model revealed otherwise. Furthermore, it was observed that the d-q axis voltages and currents of the proposed model exhibit oscillations during motor acceleration time because of the dynamics of alignment but attain constant values during the time that motor speed is constant. The proposed model is easier to solve because the rotor dynamics are described by one equation instead of two equations as in the case of the standard d-q reference frame model.